Penerapan Soal Four Tier untuk Mengidentifikasi Miskonsepsi Siswa pada Materi Aktivitas Jantung dan Pembuluh Darah - Syarafina Syarafina; Zainul Mustofa; Trio Ageng Prayitno (Program Studi Pendidikan Biologi, FKIP Unpas,, 2020)
The activity of the heart and blood vessels is material that is close to the daily activities of every human being. The importance of understanding this concept has not been understood correctly and sometimes causes misconceptions. The main purpose of this study is to identify misconceptions experienced by students in the material of heart and blood vessel activity. Case study research is used to answer it. The research subjects consisted of 97 VIII grade students from 3 schools located in Malang and Tulungagung. The study was conducted in the 2019/2020 school year. The results showed that there were 9.3% of students experiencing misconceptions on cardiac activity material, 22.7% of students experiencing misconceptions related to pulmonary arteries, 38.2% of students experiencing misconceptions related to pulmonary veins, 23.7% of students experiencing misconceptions related to arteries, and 16.5% of students experience misconceptions in distinguishing arteries and veins. In answering a series of questions about heart and blood vessel activity, students are more likely to use p-prime than their scientific knowledge.